MONITORING NILAI SUHU DAN KELEMBABAN UDARA RUANG PERAWATAN PASIEN COVID-19 BERBASIS IoT - Fajar Yumono; Danang Erwanto (Electro Luceat, 2021)
The Covid-19 outbreak is an unresolved problem because it is a new disease, so that a definite control formula is still being pursued, including by providing vaccines. There are no specific medical prescriptions for Covid-19 patients, and many experiments are carried out to achieve healing. This study offers observations of temperature and humidity in the treatment room for Covid-19 patients because temperature and humidity greatly affect the patient's recovery. The application of the Internet of Things with the nodeMCU ESP8266 module can make observations with location distances for security. These results will empirically obtain an average value for temperature and humidity in the treatment room for Covid-19 patients which can be used as a reference in other treatment rooms, especially for those who are self-isolating. From the test results of the instrument system, good results were obtained, and the percentage change in sensor readings in the temperature test sample was 3.8% and air humidity was 3.2% to the average value, and the instrument system was tested for 15 consecutive days. and the sample was taken 3 days to obtain a stable value.